Tolvaptan in Heart Failure: A Review - Kiran, Dr. Mayuresh; Shah, Ms. Priyanka (International Journal of Innovative Research in Medical Science, 2017)
There have been strong evidences that Hyponatremia (HN) often parallels the severity of cardiac dysfunction and is further exacerbated by reduction in glomerular filtration rate and arginine vasopressin dysregulation. HN is related with significant morbidity and mortality, and as such suitable treatment is necessary. HN is extensively different conditions and the fact that HN is managed by a broad variety of approaches to diagnosis and to treat. The development of Tolvaptan, an oral drug that is selective for V2receptors blockade in the renal collecting duct, has changed the management of several accompanying disorders that is in the treatment of heart failure (HF), the syndrome of inappropriate antidiuretic hormone secretion (SIADH), chronic kidney diseases (CKD) and in autosomal dominant polycystic kidney disease (ADPKD). The increased use of Tolvaptan has led to several studies assessing different parameters demonstrating the severity and the cause of dysfunctions. This paper is an analysis of both the clinical studies as well as previous literature, in order to aid appropriate clinical use of Tolvaptan in patients. With proper monitoring of serum sodium, Tolvaptan may be safely intensified from 15mg once daily to a maximum effective dose of 60mg once daily for multiple days, to achieve optimal aquaretic effects.